The influence of chemical etching on porous structure and mechanical properties of the Ti6AL4V Functionally Graded Porous Scaffolds fabricated by EBM; Materials Chemistry and Physics; Vol. 275 - Surmeneva M. A. Maria Alexandrovna; Khrapov D. Dmitriy; Prosolov K. A. Konstantin Alexandrovich; Kozadayeva M. Maria; Koptyug A. V. Andrey Valentinovich; Volkova A. P. Anastasia Petrovna; Paveljeva A. A. Aleksandra Andreevna; Surmenev R. A. Roman Anatolievich (2022, 2022)
Title screen